GAMBARAN JUMLAH ERITROSIT PADA PASIEN SUSPEK COVID-19 DI RSUD KOTA KENDARI - Umar, Ani; Wenty, Darmayanita; Salni, Salni (Jurnal Analis Kesehatan Kendari, 2024)
ABSTRACT Red blood cell or called Erythrocyte is red blood that has the most number of blood cells in the human body. The number of red blood cells can provide information that indicates the presence of hematological disordes. Hematological disorder is interference with the formation of red blood cells, including a decrease and increase in the number of cells (polycythaemia). Reduction in the number of red blood cells is found in chronic diseases, such as: liver disease, anemia, and leukemia, while polycythemia is found in patients with diarrhea, severe dehydration, burns, and heavy bleeding. The purpose of this study was to determine description of erythrocyte amounts in covid-19 suspected patients by using descriptive research, and sampling with total sampling from June -July 2020. The sample of this study was the result of examination of the number of erythrocytes in patients with suspected Covid-19. The results of the study provided a high number of erythrocytes found in patients with suspected Covid-19, as many as 7 patients (26%), the number of erythrocytes in patients with suspected Covid-19 was low, as many as 1 patient (4%), and the normal erythrocytes in patients with suspected Covid-19 was 19 patients (70%). key words: Erythrocyte, Covid-19, Number of Erythrocytes. ABSTRAK Sel darah merah atau disebut juga eritrosit merupakan sel darah yang jumlahnya terbanyak dalam tubuh manusia. Jumlah sel darah merah dapat memberikan informasi yang mengindikasikan adanya gangguan sel darah. Gangguan sel darah adalah gangguan pada pembentukan sel darah merah, meliputi penurunan dan peningkatan jumlah sel (polisitemia). Penurunan jumlah sel darah merah ditemukan pada penyakit kronis, seperti penyakit hati, anemia, dan leukemia, sedangkan polisitemia ditemukan pada penderita diare, dehidrasi berat, luka bakar, maupun pendarahan berat. Tujuan penelitian ini untuk mengetahui gambaran jumlah eritrosit pada pasien suspek Covid-19. Jenis penelitian ini adalah deskriptif dan pengambilan sampel dilakukan dengan total sampling yang merupakan data suspek Covid-19 di RSUD Kota kendari pada bulan juni-juli 2020. Sampel penelitian ini adalah data hasil pemeriksaan jumlah eritrosit pasien suspek Covid-19. Hasil penelitian menunjukkan jumlah eritrosit yang tinggi dijumpai pada pasien suspek Covid-19 yaitu 7 pasien (26%), jumlah eritrosit pada pasien suspek Covid-19 yang rendah yaitu 1 pasien (4%), dan jumlah eritrosit yang normal pada pasien suspek Covid-19 yaitu 19 pasien (70%). Kata Kunci : Eritrosit, Covid-19, Jumlah Eritrosit.